STEROID-INDUCED ANAPHYLAXIS - A, Umamaheswari; K, Bhuvaneswari; S, Ramalingam (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â To report a severe adverse drug reaction (ADR) due to administration of injection hydrocortisone sodium succinate and to explore the possibility of an association between injection hydrocortisone and the severe ADR. After getting ethics approval from the institution, ADR form and patient's clinical record from the Department of Cardiology, in a Private Medical College was received. In that, it was recorded as a 75-year-old male patient, a case of unstable angina with troponin T - positive, was posted for coronary angiogram developed a severe reaction to intravenous (IV) hydrocortisone 100 mg stat, given to prevent allergy to contrast dye used in the procedure. 5 minutes after drug administration, he developed sudden itching all over the body, hypotension blood pressure: 60 mmHg and swelling of lips. No other drugs had been given at that time. The patient was already on aspirin 150 mg, clopidogrel 75 mg, and atorvastatin 80 mg, and enoxaparin 40 mg. The procedure was abandoned, and the patient was given injection pheniramine maleate 45.5 mg IV, injection dopamine 10 mcg/kg/min IV. He symptomatically improved within 6 hrs. Causality analysis using the WHO scale categorizes it as probable, as anaphylaxis occurred immediately after administration of hydrocortisone, no other drugs were given at that time, and rechallenge was not done. Very few cases of various steroid-induced anaphylaxis have been reported worldwide. This one among the rare ADR report may be due to the steroid or the excipients in the preparation. Skin prick test or in vitro (radioallergosorbent test assay) test can be done immediately to confirm the causative allergen in this case and would also help in identifying specific agents that will be tolerated in the future treatment.